Development of Talent Management for Business Ventures in Motorsport - Syarizal Abdul Rahim; Norailis Ab. Wahab; Razli Che Razak; Mohd Hafzal Abdul Halim (Insights into Economics and Management Vol. 10, 2021)
Talent has emerged as a potentially important source of competitive advantage in today’s corporate world. It is the foundation for establishing an organisation that is capable of learning, inventing, and adapting, as well as implementing new procedures. Talent management is defined as "extra management processes and opportunities put in place for persons in the business who are seen to be gifted." This article aims to provide aguidance for racers who want to grow their businesses by extending their success on racing tracks to business routes. This post is based on data acquired from in-depth interviews with three business owners who are also racers. During the interview, opinion on benchmarking via talent in motorsports and companies was requested. This research showed the necessity of talent management as seen through the lens of how great performers in motorsports have managed to drive their businesses while still generating great achievements on the race courses. The function of the business owner will be to act as a catalyst for increasing the output from bike manufacture. They might also help fund research and development so that nice motorcycles with high performance and durability may be produced.